Noncontiguous finished genome sequence and description of Paenibacillus ihumii sp. nov. strain AT5. (March 2016) - Togo, A.H.; Khelaifia, S.; Lagier, J.-C.; Caputo, A.; Robert, C.; Fournier, P.-E.; Maraninchi, M.; Valero, R.; Raoult, D.; Million, M.
Abstract: Paenibacillus ihumii sp. nov. strain AT5 (= CSUR 1981 = DSM 100664) is the type strain of P. ihumii. This bacterium was isolated from a stool sample from a morbidly obese French patient using the culturomics approach. The genome of this Gram-negative, facultative anaerobic, motile and spore-forming bacillus is 5 924 686 bp long. Genomic analysis identified 253 (5%) of 3812 genes as ORFans and at least 2599 (50.03%) of 5194 orthologous proteins not shared with the closest phylogenetic species.